2020
DOI: 10.3390/biom10081135
|View full text |Cite
|
Sign up to set email alerts
|

A Shift in Glycerolipid Metabolism Defines the Follicular Fluid of IVF Patients with Unexplained Infertility

Abstract: Follicular fluid (FF) constitutes the microenvironment of the developing oocyte. We recently characterized its lipid composition and found lipid signatures of positive pregnancy outcome after in vitro fertilization (IVF). In the current study, we aimed to test the hypothesis that unexplained female infertility is related to lipid metabolism, given the lipid signature of positive-outcome IVF patients we previously found. Assuming that FF samples from IVF patients with male factor infertility can represent a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Although follicular glucose level didn’t show difference between the two groups of different ages, lactate level in the follicular fluid was increased in advanced age group suggesting increased anaerobic glycolysis. Lipid metabolism disorder was proved to be associated with female reproductive and endocrine functions ( 24 ). The current literature indicates that higher lipolysis and lower lipogenesis enhance the delivery of lipid metabolites ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although follicular glucose level didn’t show difference between the two groups of different ages, lactate level in the follicular fluid was increased in advanced age group suggesting increased anaerobic glycolysis. Lipid metabolism disorder was proved to be associated with female reproductive and endocrine functions ( 24 ). The current literature indicates that higher lipolysis and lower lipogenesis enhance the delivery of lipid metabolites ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…A research found that mouse cumulus-oocyte complexes exposed to lipid-rich FF during their maturation had increased oocyte lipid content, induction of endoplasmic reticulum stress markers, and impaired oocyte nuclear maturation [ 17 ]. TG accumulation in the FF was also correlated to the levels of adipokines and proinflammatory cytokines in FF, implying inflammatory processes in the FF that are caused by high TG levels and may also attenuate oocyte development [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…and may also attenuate oocyte development [18]. That was why PCOS patients always have the impaired oocyte development in ART.…”
Section: Discussionmentioning
confidence: 99%
“…A research found mouse cumulus-oocyte complexes (COCs) exposed to lipid-rich FF during their maturation had increased oocyte lipid content, induction of endoplasmic reticulum stress markers, and impaired oocyte nuclear maturation [17]. TG accumulation in the FF were also correlated to the levels of adipokines and proin ammatory cytokines in FF, implying in ammatory processes in the FF that are caused by high TG levels and may also attenuate oocyte development [18]. That was why PCOS patients always have the impaired oocyte development in ART.…”
Section: Discussionmentioning
confidence: 99%